Percutaneous minimally invasive fetoscopic surgery for spina bifida aperta. Part III: neurosurgical intervention in the first postnatal year. (2nd February 2016) - Graf, K.; Kohl, T.; Neubauer, B. A.; Dey, F.; Faas, D.; Wanis, F. A.; Reinges, M. H. T.; Uhl, E.; Kolodziej, M. A.
ABSTRACT: Objective: To evaluate the need for postnatal neurosurgical intervention after fetoscopic patch coverage of spina bifida aperta (SBA). Methods: This was a retrospective analysis of a cohort of 71 fetuses which underwent minimally invasive fetoscopic patch coverage of SBA between 21 + 0 and 29 + 1 weeks of gestation. Postnatal neurosurgical procedures were classified into two types: re‐coverage of the SBA within the first 3 months following birth, and shunt placement as treatment of associated hydrocephalus within the first year. Results: Location of the SBA was lumbosacral in 59 cases, lumbar in seven, thoracic in three and sacral in two. In total, 20/71 (28%) patients underwent early postnatal neurosurgical intervention by means of re‐coverage of the SBA. This was performed because of cerebrospinal fluid leakage in seven (35%), adhesions with functional deterioration in three (15%), incomplete coverage in five (25%) and skin defect in five (25%) cases. Ventriculoperitoneal shunt placement within 1 year was required in 32 (45%) cases and was preceded by ventriculostomy in two. Three (4%) infants needed Chiari decompression surgery in the first 12 months following birth, because of syringomyelia or gait disturbance. Conclusions: Fetoscopic patch coverage of SBA may require postnatal re‐coverage in some cases. In most cases, conservative wound treatment shows good results, without requiring neurosurgical intervention. The low 1‐year‐shunt rate is comparable to data of the Management of Myelomeningocele Study and lower compared with published data of patients with postnatal only coverage of SBA. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.